(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kowalewski P. V., Koshevaya L. V. Osobennosti formings of corporate personality qualities of students by facilities of physical education. In the article the features of process of forming of personality qualities of students are presented by facilities of physical education in the context of corporate culture. Being a sustems factor, a corporate culture of any organization is a basic constituent, that allows organization to be successful in the conditions of market relations. The ways of forming of corporate qualities of students are rotined as future graduating students, oriented to the market of labour.